Measuring the potential distribution inside soft organic semiconductors with a scanning-tunneling microscope - Kemerink, Martijn; Offermans, Peter; Koenraad, Paulus M.; Duren, Jeroen Karolus Johannes van; Janssen, René A. J.; Salemink, Huub W.; Wolter, Joachim H. (Physica. E, Low-dimensional systems & nanostructures, 2002)
For the first time, we directly measured the potential distribution inside organic semiconductors. Combined spectroscopic measurements are performed on MDMO-PPV layers on Au and Yb substrates, using a scanning-tunneling microscope. The results are analyzed with a model that treats both current injection and bulk transport in detail. It is found that tip height-bias curves, which are taken by following the height of the STM tip as a function of bias, while the STM feedback system is active, reflect the potential distribution between tip and sample electrode.